Understanding the factors leading to high prevalence of teenage pregnancies in the four aspirational Districts of Assam, Namely Goalpara, Barpeta, Dhubri, and darrang - Kastaurika Saikia; Sharma Nisha; Sharma Malvika; K B Hegde Shailendra; Deshmukh Ashwin (Wolters Kluwer Medknow Publications, 2023)
Background: The prevalence of teenage pregnancy in Assam is higher than the national average as per both NHFS-4 and NHFS-5. Four districts in Assam, falling under the NITI-Aayog Aspiration Districts Transformation program of 2018, namely, Goalpara, Barpeta, Darrang, and Dhubri, have a prevalence of teenage pregnancy at levels higher than the state's average (12% as per NHFS-5). Teenage pregnancy affects several health and nutritional indicators. Objectives: The objective of the study was to identify the factors associated with teenage pregnancies in the Aspirational Districts of Assam in both social and public health contexts. Methods: A comparative cross-sectional study was carried out across these four districts, with sample size of teenage pregnant women as 388 and an equal number of controls. Results: The study presents several factors to be statistically significant, viz., lower level of education of the teenage mothers or their spouses and lesser access to adequate health-related information by teenage mothers. Furthermore, less number of teenage mothers are aware of contraceptive availability and face objection from spouses to use contraception. A unique factor presented by the study is the higher elopement rate among teenage mothers. Conclusion: Many of the factors upheld by the study are rooted in social and cultural fabric of the communities and could be addressed by mobilizing local institutions like panchayat and religious bodies to act as deterrence to teenage marriages in the communities. Men should also be brought into the fold of discussions on this sensitive subject through information and awareness generation.